Refleksi nilai-nilai kultural dan linguistik dalam situs haji - Gayda Bachmid (Masyarakat, Kebudayaan dan Politik, 2015)
A hidden value reflection in pilgrim ritual texts and pilgrim sites is the creation of the clearest thinking pattern and human behavior through liturgy domain. This is very potential and strategic in the framework of spreading, enlightenment, consolidation and full experience of religious value actualization and faith in life. This research was limited to internal and external linguistic aspects. These two elements were studied and traced through verbal messages (prayer texts). Qualitative method was used through eclectic application, Arabic language theory combination, and semiotics. Research findings indicate there are insya‟thalabi and insya‟ ghairi thalabi category forms. Insya‟ thalabi consists of 124 lexical requests in the form of imperative and prohibition. Insya‟ ghairi thalabi consists of 201 words of admiration, greatness, and adoration to the Creator. Through Badi‟ science approach, 103 beautiful rhyming forms and 7 repetitive words are found. There are also pledge and promise sentences in the form of declarative, imperative and oath taking in the name of God. The site historical contemplation reflects the values of self-correction, servitude and self-control. The cultural values of the site historical reflection results experienced by the ritual agents are ethics, moral, selfawarwnrss, self–correction, servitude, self-control, spiritual cleansing from disavowal, faith, and spitefulness. Human social valued are democratization, equality, and philosophy